Demarginalizing the Intersection of Race and Sex: A Black Feminist Critique of Antidiscrimination Doctrine, Feminist Theory and Antiracist Politics - Crenshaw, Kimberlé (University of Chicago, 1989)
One of the very few Black women's studies books is entitled All the Women Are White; All the Blacks Are Men, But Some of Us are Brave. I have chosen this title as a point of departure in my efforts to develop a Black feminist criticism because it sets forth a problematic consequence of the tendency to treat race and gender as mutually exclusive categories of experience and analysis. In this talk, I want to examine how this tendency is perpetuated by a single-axis framework that is dominant in antidiscrimination law and that is also reflected in feminist theory and antiracist politics.